What and How of Standards Information - Prasad, K. N. (Journal of Information and Knowledge, 2014)
The paper discusses the usefulness of Standards as information carriers. It discusses the different information retrieval tools offered by the various national and international Standards bodies. The standardization activities in library, documentation and information fields are related.